An Ayurvedic Approach in the Management of Vatarakta (International Journal of Ayurveda and Pharma Research, 2023)
Ayurveda, since beginning emphasizes on the importance of wholesome lifestyle for maintenance of health and prevention of several diseases. Changing dietary habit with fast food culture, lack of physical activities and stressful environmental factors are the leading cause of many lifestyle disorders and Vatarakta is one of them. It is characterized by severe pain, swelling, stiffness, inflammation and burning sensation of affected joints. It may be correlated with Gout in contemporary science. A 45 years old female patient visited Panchakarma OPD of S.V.S.P hospital with severe pain, mild oedema, tingling sensation in the joints of hand and leg bilaterally associated with burning sensation and discolouration of both feet since 3 month. She was treated with Shamana aushadhi, Panchakarma therapy and specific dietary intervention for 30 days. Encouraging improvement in both subjective and objective criteria was obtained. This case study may ignite a positive hope for individual suffering from Vatarakta.